Body clocks, jet lag, and sports performance. The times of our lives - Eichner, E. R. (Current Sports Medicine Reports, 2020)
Today, it is easy to get "out of sync" with our world. This has implications for health and sports. As our planet rotates to create a day-night cycle, we have a tiny body clock (rumored to be in the hypothalamus) that follows that cycle. This inborn "circadian rhythm" seems to orchestrate most of our biological functions, including sleep, mood, metabolism, temperature, alertness, vigor, heart rate, blood pressure, bronchial caliber, urine excretion, and hormone output. As we wax and wane in these vital functions, our sports performance may wax and wane in concert. This field of study - body clocks and sports performance - is sweeping and nuanced, but let me offer a few examples that seem relevant for athletes.